Systematic literature review and meta-analysis of clinical outcomes and prognostic factors for melanoma brain metastases - Tan, Xiang-Lin; Le, Amy; Scherrer, Emilie; Tang, Huilin; Kiehl, Nick; Han, Jiali; Jiang, Ruixuan; Diede, Scott J.; Shui, Irene M. (Frontiers in Oncology, 2022)
Background: More than 60% of all stage IV melanoma patients develop brain metastases, while melanoma brain metastases (MBM) is historically difficult to treat with poor prognosis. Objectives: To summarize clinical outcomes and prognostic factors in MBM patients. Methods: A systematic review with meta-analysis was conducted, and a literature search for relevant studies was performed on November 1, 2020. Weighted average of median overall survival (OS) was calculated by treatments. The random-effects model in conducting meta-analyses was applied. Results: A total of 41 observational studies and 12 clinical trials with our clinical outcomes of interest, and 31 observational studies addressing prognostic factors were selected. The most common treatments for MBM were immunotherapy (IO), MAP kinase inhibitor (MAPKi), stereotactic radiosurgery (SRS), SRS+MAPKi, and SRS+IO, with median OS from treatment start of 7.2, 8.6, 7.3, 7.3, and 14.1 months, respectively. Improved OS was observed for IO and SRS with the addition of IO and/or MAPKi, compared to no IO and SRS alone, respectively. Several prognostic factors were found to be significantly associated with OS in MBM. Conclusion: This study summarizes pertinent information regarding clinical outcomes and the association between patient characteristics and MBM prognosis.